The Role of Entrepreneurial Mindset and Innovation in Enhancing Students’ Growth and Engagement - Emmanuela Nneka Clinton (Journal of Social Science and Humanities, 2026)
This study examined the role of entrepreneurial mindset and innovation in enhancing students’ growth and engagement, focusing on higher education in Nigeria. Using a qualitative content analysis of 25 peer-reviewed papers published between 2015 and 2025, the study applied the PRISMA framework to ensure rigor and relevance. Findings revealed that an entrepreneurial mindset improved self-efficacy, motivation, and persistence, while innovation fostered creativity, problem-solving, and active engagement in learning. Importantly, the combined effect of mindset and innovation produced synergistic outcomes that significantly enhanced student growth and preparedness for post-graduation challenges. The study concludes that embedding entrepreneurial and innovative practices into university curricula is essential for addressing Nigeria’s educational and socio-economic gaps. Policy recommendations call for mandatory entrepreneurship-innovation modules, curriculum reforms, and institutional funding support to ensure sustainable student engagement and national development.